Community Empowerment in Developing Village Potentials in Ecotourism Activities in Abiansemal Badung Bali - I Wayan Wesna Astara; I Nyoman Putu Budiartha; I Wayan Rideng; Made Bagoes Wiranegara Wesna; Made Setiasa (Fakultas Hukum, Universitas Warmadewa, 2023)
American writer wrote a book, dubbing the island of Bali